2021
DOI: 10.1186/s12951-021-01083-0
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting polymer nano-radiopharmaceutical for combined radio-photothermal therapy of pancreatic tumor

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is a devastatingly malignant tumor with a high mortality. However, current strategies to treat PDAC generally have low efficacy and high side-effects, therefore, effective treatment against PDAC remains an urgent need. Results We report a semiconducting polymer nano-radiopharmaceutical with intrinsic photothermal capability and labeling with therapeutic radioisotope 177Lu (177Lu-SPN-GIP) for combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In vitro and in vivo experiments showed that the combined treatment could effectively combat PDAC and improve the therapeutic effect. Semiconductor polymer NPs (SPN) composed of completely organic compounds have become photothermal agents for cancer treatment [ 119 , 120 ]. Compared with other inorganic nanomaterials, SPNs have unique characteristics such as better biocompatibility, and higher photothermal conversion efficiency and controllability.…”
Section: Well-designed Nanosystems For Different Pdac Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo experiments showed that the combined treatment could effectively combat PDAC and improve the therapeutic effect. Semiconductor polymer NPs (SPN) composed of completely organic compounds have become photothermal agents for cancer treatment [ 119 , 120 ]. Compared with other inorganic nanomaterials, SPNs have unique characteristics such as better biocompatibility, and higher photothermal conversion efficiency and controllability.…”
Section: Well-designed Nanosystems For Different Pdac Therapeuticsmentioning
confidence: 99%
“…The utilization of SPNs for PTT has been well explored, but there are few reports on combination therapy. In their study, Shi et al reported a 177 Lu-labeled glucose-dependent insulinotropic polypeptide-targeting SPN for combined radiotherapy and PTT of PDAC [ 120 ]. As a result, these combined treatment techniques complemented each other and provided superior results to PTT or radiotherapy alone.…”
Section: Well-designed Nanosystems For Different Pdac Therapeuticsmentioning
confidence: 99%
“…, 131 I, 99m Tc, and 177 Lu) to observe pharmacokinetics and biodistribution of radioactive drugs. 361–363 For instance, Cheng et al designed radioisotope 131 I-labeled Au nanoframeworks ( 131 I-AuNFs) for synergistic RIT/PTT of breast cancer. 364 Specifically, the AuNFs were coated with polydopamine (PDA) and further chelated with 131 I to construct 131 I-AuNFs (Fig.…”
Section: Image-guided Techniques For Precision Rtmentioning
confidence: 99%
“… 54 Shi et al designed a nano-radiopharmaceutical ( 177 Lu-SPN-GIP) that displayed greater tumor-killing impact than conventional RT and considerably improved therapeutic outcomes. 55 Consequently, combining nanomaterials-induced ferroptosis and ionizing radiation will be a viable approach. Because it can improve stability, cell uptake rate and tumor site retention time.…”
Section: Combined Ferroptosis-driven Nanomaterials and Ionizing Radia...mentioning
confidence: 99%